2011
DOI: 10.1007/s00429-011-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative in vivo MRI measurement of cortical development in the fetus

Abstract: Normal brain development is associated with expansion and folding of the cerebral cortex following a highly orchestrated sequence of gyral-sulcal formation. Although several studies have described the evolution of cerebral cortical development ex vivo or ex utero, to date, very few studies have characterized and quantified the gyrification process for the in vivo fetal brain. Recent advances in fetal magnetic resonance imaging and post-processing computational methods are providing new insights into fetal brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
145
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 57 publications
9
145
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) studies in CHD fetuses show smaller total brain volumes (adjusted for gestational age and weight) and abnormal brain metabolism, as well as delayed cortical development and folding. [27][28][29][30][31] At birth, brain maturation in neonates with HLHS or TGA is delayed by ∼1 month compared with a normative sample. 29 Postnatal MRI studies have shown All characteristics from Table 1 except preoperative mechanical ventilation were considered for inclusion in the models.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies in CHD fetuses show smaller total brain volumes (adjusted for gestational age and weight) and abnormal brain metabolism, as well as delayed cortical development and folding. [27][28][29][30][31] At birth, brain maturation in neonates with HLHS or TGA is delayed by ∼1 month compared with a normative sample. 29 Postnatal MRI studies have shown All characteristics from Table 1 except preoperative mechanical ventilation were considered for inclusion in the models.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that even in the absence of structural brain injury, the developmental trajectory of the preterm brain is altered over the third trimester. Evidence of clinical 4 .01 * 14.17 ± 1.6 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] 13.91 ± 2.7 [8][9][10][11][12][13][14][15][16][17][18][19][20] .66…”
Section: Discussionmentioning
confidence: 99%
“…We prospectively enrolled healthy volunteers with singleton pregnancies and a normal pregnancy history, with normal clinical laboratory and ultrasound studies during the current pregnancy [12,25,[27][28][29] . Exclusion criteria included multiple gestations, known or suspected genetic or chromosomal abnormalities, as well as any maternal contraindication for MRI, including physical (e.g., metal implants) or psychosocial (e.g., claustrophobia) contraindications.…”
Section: Patientsmentioning
confidence: 99%
“…3D volumetric techniques provide more accurate results compared to the standard 2-dimensional (2D) biometric measures [16,22,23] . Together these techniques provide a multifaceted understanding of the developing brain, its regional and tissue-specific growth, microarchitecture, and evolving connectivity [12,[24][25][26] . These emerging quantitative MRI techniques are allowing us for the first time to identify the onset and evolution of acquired and dysgenetic fetal brain lesions, and allowing for more accurate prognostication of functional outcomes [7,26] .…”
mentioning
confidence: 99%